The Potential Role of Humans in the Transmission Cycle of Leishmania major (Kinetoplastida: Trypanosomatidae), the Causative Agent of the Old World Zoonotic Cutaneous Leishmaniasis. Issue 6 (13th August 2018) - Fatemi, Mahboubeh; Yaghoobi-Ershadi, Mohamad Reza; Mohebali, Mehdi; Saeidi, Zahra; Veysi, Arshad; Gholampour, Fatemeh; Akhondi, Behnaz; Karimi, Ameneh; Arandian, Mohamad Hossein; Amin Mohammadi, Akram Mir; Rassi, Yavar; Zahraei-Ramazani, Alireza; et al.
Abstract: Zoonotic cutaneous leishmaniasis (ZCL) due to Leishmania major (Yakimoff and Schokhor, 1914) is known as a neglected tropical disease, transmitted by Phlebotomus papatasi (Scopoli, 1786) in North Africa and the Middle East. The main reservoirs of ZCL are desert gerbils and the role of humans as a reservoir host of the disease is not clearly defined and is therefore investigated in this study. In order to achieve this objective, Ph. papatasi sand flies were allowed to take blood through indirect blood sources (human, Rhombomys opimus (Lichtenstein, 1823) (great gerbil), and BALB/c mice) using artificial feeding or direct xenodiagnoses from ZCL patients. To detect Leishmania promastigotes inside digestive canal, blood-fed sand flies were dissected and examined under light microscope and then confirmed by nested-PCR. In indirect xenodiagnoses, promastigote forms of Leishmania parasite were observed in 7.1%, 12%, and 13.6% of sand flies which fed on Rh. opimus, BALB/c mice, or human blood sources, respectively. In direct xenodiagnoses, among 93 female lab-reared sand flies which fed on active L. major lesion(s), 2.1% Leishmania infection was subsequently observed in the sand flies. No infection was detected in those sand flies that fed on nonlesioned skin of CL patients. Humans can serve as a reservoir of ZCL since the data indicate that Ph. papatasi is able to acquire L. major parasites from an active lesion of ZCL patients and the parasites can complete metacyclogenesis in the sand fly.